The Vanguard Study: Human Performance Evaluation of UK National Organ Retrieval Service Teams Utilizing a Single Scrub Practitioner in Multiorgan Retrieval. Issue 5 (29th June 2020) - Morozova, Gala; Martindale, Amanda B.; Richards, Hugh; Stirling, John; McIntyre, Cecelia; Currie, Ian S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The National Organ Retrieval Service (NORS) 2015 review recommended a single scrub practitioner provide support simultaneously to abdominal and cardiothoracic teams in UK multiorgan retrieval. Previously, this model had been used only by the combined abdominal and cardiac team in Scotland. This study reports the impact on performance as part of the Vanguard project, which utilized the single scrub practitioner role with 5 NORS teams, to determine applicability United Kingdom wide. Methods: Participants comprised members of abdominal (n = 56) and cardiothoracic (n = 54) teams attending UK thoraco-abdominal retrievals. Data were collected by validated psychometric scales to assess individual workload, anxiety, confidence, demands/coping resources, and teamwork. Additional data were collected through open comments and quantitative data describing context and outcome of retrieval. Results: Abdominal and cardiothoracic teams showed different responses when using single (Vanguard) or dual scrub practitioners (Standard). Vanguard configuration was associated with significantly higher anxiety for abdominal but not cardiothoracic teams. Perceived workload increased for abdominal teams during Vanguard but decreased for cardiothoracic teams. Scrub practitioners reported elevated anxiety and decreased confidence in retrievals using Vanguard configuration. Conclusions: This is the first large study examining human performance during organ retrieval in the United Kingdom. Despite previous regional success, this study showed a significant negative impact of the single scrub practitioner when extrapolated widely to UK teams. As a result of this study, NORS declined to implement the single scrub model. These data support the use of human performance analysis as an essential part of successful development in organ retrieval practice.